Student Voice and English Achievement Among Indonesian Ninth Graders: An Exploratory Correlational Study - Hidayanti, Vemi; Kholid, Idham; Rahmawati, Istiqomah Nur (Universitas Islam Negeri Raden Intan Lampung, 2026)
In Indonesian secondary schools, low student participation and constrained classroom interaction remain persistent impediments to English as a Foreign Language (EFL) learning outcomes. This study examined the association between student voice—defined as students' perceived opportunities to express opinions, contribute to classroom decisions, and receive teacher responsiveness—and English achievement among ninth-grade students at SMP Negeri 1 Tanjungsari, South Lampung, Indonesia. A quantitative correlational design was employed, with student voice operationalized through a nine-item, 4-point Likert-type questionnaire (Cronbach's α = .853) and English achievement measured via school-recorded semester final scores. Assumptions for Pearson's r were satisfied: both variables approximated normality (Shapiro–Wilk: p > .10), a linear relationship was indicated, and no extreme outliers were detected. The analysis revealed a small, statistically non-significant association between student voice and English achievement, r(18) = .172, p = .469, 95% CI [−.30, .58], r² ≈ .03. Although the correlation did not attain significance, the findings suggest that student voice may exert an indirect influence on English achievement through motivational and affective pathways—including self-efficacy, confidence, and engagement—rather than operating as a direct predictor of test performance. The study contributes empirical evidence from an under-researched Indonesian EFL context, affirming the need to integrate student-voice practices with responsive instructional strategies and to examine indirect effects via mediation models in future research.